Planar channelling of relativistic electrons in half-wave silicon crystal and corresponding radiation; Journal of Physics: Conference Series; Vol. 732 : Radiation from Relativistic Electrons in Periodic Structures (RREPS2015) - Takabayashi Yu. Yushi; Bagrov V. G. Vladislav Gavriilovich; Bogdanov O. V. Oleg Viktorovich; Pivovarov Yu. L. Yuriy Leonidovich; Tukhfatullin T. A. Timur Ahatovich (Monochromatic X- and Gamma Beams Produced at Electron Accelerators, 2016)
Title screen